Distribution of class 1 integrons in historic and contemporary collections of human pathogenic Escherichia coli - Maiden, M; Suetterlin, S; Bray, J; Tano, E (Public Library of Science, 2020)
Integrons play a major role in the evolution and spread of antimicrobial resistance in human pathogens, including Escherichia coli. This study describes the occurrence of class 1 integrons in human pathogenic E. coli, in three isolate collections involving three periods from the last 100 years (i) the Murray collection (n = 58 bacteria isolated from the 1910s to 1940s); (ii) the E. coli reference (ECOR) collection (n = 37 isolates mainly from the 1980s); and (iii) a recently assembled collection (n = 88 isolates obtained in 2016). High-quality whole genome sequences (WGSs) were available for all isolates. Integrons were detected in the WGSs with the program IntegronFinder and the results compared with three established methods: (i) polymerase chain reaction detection of the integrase gene; (ii) BLAST searching using draft genomes; and (iii) mapping of short reads. No integrons were found in any of the Murray Collection isolates; however, integrons were present in 3% of the isolates from ECOR collection, assembled in the 1980s, and 26% of the isolates from the 2010s. Similarly, antimicrobial resistance determinants were not present in the Murray Collection isolates, whereas they were present in 19% of the ECOR Collection isolates and in 55% of the isolates obtained in during the 2010s.